2022
DOI: 10.3390/agriculture12010104
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Milking Systems in the Production of Parmigiano Reggiano Cheese: Effects on the Milk Quality and on Cheese Characteristics

Abstract: The adoption of innovative processes, such as the automatic milking system (AMS), in the production of typical PDO cheeses, such as Parmigiano Reggiano, needs to be evaluated and tested, to verify its influence on milk quality and the typicality of the product. The present research was aimed to study the effect of the introduction of the AMS on the cheesemaking characteristics of the milk and the ripening process and the sensory properties of the Parmigiano Reggiano PDO cheese. Six cheesemaking trials were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The nutritional content of the milk used in the present study exhibited nutrient levels similar to the Italian average for Holstein cow milk quality, especially in the context of Parmigiano Reggiano production [50][51][52]. The inclusion of tannins in milk in preweaning calves did not affect the growth curve over 30 days of the trial.…”
Section: Discussionsupporting
confidence: 60%
“…The nutritional content of the milk used in the present study exhibited nutrient levels similar to the Italian average for Holstein cow milk quality, especially in the context of Parmigiano Reggiano production [50][51][52]. The inclusion of tannins in milk in preweaning calves did not affect the growth curve over 30 days of the trial.…”
Section: Discussionsupporting
confidence: 60%
“…The peptide fraction also evolves throughout typical pathways during the ripening period of GP cheese. Consistently, it was demonstrated that changes in the manufacturing process, such as milk pasteurization or de-bacterization by centrifugation or the usage of microbial coagulant, may affect these pathways in different ways [35,36]. The relevance of peptide fraction as a quality parameter of cheese ripening has been also highlighted in Parmigiano Reggiano cheese [16,37].…”
Section: Discussionmentioning
confidence: 80%
“…Even when looking at the mean CC of all milk samples from farms using milking parlors or pipe milking systems (4.2 ± 0.4 log colonies/mL raw milk), the mean CC of milk samples from farms with an AMS (4.2 ± 0.3 log colonies/mL raw milk) is comparable. Although most studies report an increase in CC after transitioning to an AMS, not all do, and there are several parameters that affect the CC in addition to the milking system, such as barn hygiene or equipment sanitation [ 39 , 43 ]. Furthermore, as we did not find any correlations between dPAB levels and the CC, the influence of an AMS on dPAB counts may be limited.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for the lower dPAB levels in AMS milk could be cleaning by backflushing or steaming between milkings. Since most dPAB strains are heat sensitive, this could be effective in preventing higher dPAB levels in AMS raw milk [ 4 , 43 , 44 ]. To the best of our knowledge, we are the first to observe this relationship between dPAB levels in raw milk and the miking system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation